Beyond Empathy: Examining the Complexities of Outpatient Satisfaction in a Resource-Constrained Setting - Hannitya Aulia Putri; Rizanda Mahmud; Wihardi Triman (Community Medicine and Education Journal, 2024)
Patient satisfaction is a critical indicator of healthcare quality, particularly in resource-constrained settings where efficient and effective care is paramount. This study aimed to explore the multifaceted nature of outpatient satisfaction at a private Indonesian hospital, moving beyond the traditional focus on empathy to understand the interplay of various service quality dimensions. A mixed-methods sequential explanatory design was employed. The quantitative phase involved a survey of 400 outpatients, measuring their satisfaction with five service quality dimensions: tangibles, reliability, responsiveness, empathy, and assurance. Data were analyzed using descriptive statistics, Importance-Performance Analysis (IPA), and gap analysis (suitability index). The qualitative phase utilized in-depth interviews and focus group discussions with patients, staff, and management to provide context and depth to the quantitative findings. While overall patient satisfaction was 82.9%, a gap analysis revealed substantial discrepancies between patient expectations and perceptions across several service quality dimensions. Tangibles, reliability, and responsiveness emerged as key areas requiring improvement. Qualitative findings highlighted extended wait times, inconsistent staff communication, and concerns about the physical environment as significant contributors to patient dissatisfaction. Achieving high levels of patient satisfaction in resource-constrained environments necessitates a comprehensive approach that addresses systemic inefficiencies and communication gaps alongside interpersonal factors like empathy. These findings underscore the need for targeted interventions to optimize resource allocation, streamline processes, and enhance staff communication skills to improve the patient experience.